(untitled) (Al-Academy, 2026)
Here is the appearance of the year for art .. everyone agrees that his history refers to the active presence of people in the business of plastic, and that any review of this history will reveal a common unit which made the historians are able to trace the humanitarian impact in the style of presentation from one generation to another. Therefore, finding a direct lineage of art series order remains in the folds of historical studies that prevailed for a long time. Perhaps can make a comparison between the human body or the emergence of what we call idiomatically (diagnosis) between the general social conditions of civilizations and between the techniques involved, such as check-moral, religious, economic, social and otherwise. There have been, in fact revolutions in the history of the human body or show his presence or not, there is a revolution with every era, and periodically with almost every century, where there is a deeper and broader changes distinguish discrimination purely physically. The physical rituals is the presence of the body distinguishing mark, which vary in their construction and their homes as the value of plastic representation, was that sought art to self associated with the Authority’s approach or what we call a metaphor articulating their own name, and if we moved to concepts such as the concept of the presence of the body. The first thing that draws attention in this area is the breakthrough of the concept of modern culture, which looks at all the standards and secretions inhabited the flesh and of seeking to confirm his presence, but the tyranny of this concept does not mean clearly and precisely clear, but it can be said that the body of the most philosophical concepts confusion and intractability for identification and find this confusion interpreted in the history of this concept in philosophical thought.